Bogdan Illich Simenach - «SISJP NAMS», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
The article is devoted to the well-known scientist, Professor, Doctor of Medical Sciences Simenach Bogdan Ilyich, who turned 95 years old June 20, 2016.